Cyclin D type does not influence cell cycle response to DNA damage caused by ionizing radiation in multiple myeloma tumours. (4th May 2016) - Smith, Dean; Mann, David; Yong, Kwee
Summary: Multiple myeloma (MM) is characterized by over‐expression of cyclin D1 (CCND1) or D2 (CCND2), which control G1 phase cell‐cycle progression. Proteolytic degradation of CCND1 (but not CCND2), resulting in G1 arrest, is reported in non‐MM cells post‐DNA damage, affecting DNA repair and survival. We examined the effect of ionizing radiation (IR) on D‐cyclin levels and cell‐cycle kinetics of MM cells, exploring differences based on D‐cyclin expression. We showed that CCND1 is downregulated, whereas CCND2 is not, following IR. This did not lead to hypo‐phosphorylation of retinoblastoma protein or G1 arrest. Both CCND1‐ and CCND2‐expressing MM cells arrested in S/G2/M, and did not differ in other cell‐cycle proteins or sensitivity to IR. When treated with a CDK4/6 inhibitor, both CCND1 and CCND2 MM cells arrested in G1 and therefore are subject to physiological regulation at this checkpoint. Immunoprecipitation showed that, despite CCND1 degradation following IR, sufficient protein remains bound to CDK4/6 to prevent G1 arrest. Aberrant expression of CCND1 driven from the IGH promoter in t(11;14) MM cells maintains progression through G1 to arrest in S/G2/M. Differential expression of D‐cyclin does not appear to affect cell‐cycle response to IR, and is unlikely to underlie differential sensitivity to DNA damage.